All High-Spin (S = 2) Iron(II) Hemes are NOT Alike - Hu, Chuanjiang (Dalton Trans, 2015)
A common structural motif in heme proteins is a five-coordinate species in which the iron is coordinated by a histidyl residue. The widely distributed heme proteins with this motif are essential for the well being of humans and other organisms. We detail the differences in molecular structures and physical properties of high-spin iron(II) porphyrin derivatives ligated by neutral imidazole, hydrogen bonded imidazole, and imidazolate or other anions. Two distinct (high spin) electronic states are observed that have differing d-orbital occupancies and discernibly different five-coordinate square-pyramidal coordination groups. The doubly occupied orbital in the imidazole species is a low symmetry orbital oblique to the heme plane whereas in the imidazolate species the doubly occupied orbital is a high symmetry orbital in the heme plane, i.e., the primary doubly-occupied d-orbital is different. Methods that can be used to classify a particular complex into one or the other state includes X-ray structure determinations, high-field Mössbauer spectroscopy, vibrational spectroscopy, magnetic circular dichroism, and even-spin EPR spectroscopy. The possible functional significance of the ground state differences has not been established for heme proteins, but is likely found in the pathways for oxygen transport vs. oxygen utilization.